Increasing trust on the law enforcement in rural communities: Lens from pro-active youth leaders - Armando A. Alviola; Jill Rose P. Ador; Jose Rene A. Cepe; Altamer Alfad Hussin; Noralyza Sakib Jaam; Ahmedkhan Aubin Jumdai; Imran H. Mangawan (Environment and Social Psychology, 2025)
Trust in law enforcement is a critical factor in building safe and resilient communities, yet rural contexts often reveal fragile relationships shaped by fear, historical trauma, and unequal treatment. This study explores how proactive youth leaders in Eastern Visayas and Mindanao, Philippines perceive local police and what initiatives they employ to strengthen collaboration. Using semi-structured interviews with 20 youth leaders and a reflexive thematic analysis approach, the study examined two objectives: (1) to explore perceptions and experiences of youth leaders regarding police-community relations, and (2) to identify strategies they use to foster trust and collaboration. Findings show that trust remains tenuous due to fear-based visibility during raids, profiling, favoritism, and cultural or linguistic distance. However, youth also recognized moments of empathy, particularly during disaster response, where police acted as allies rather than enforcers. Youth-led initiatives such as community sports leagues, peer-facilitated dialogues, and rights education workshops created safe spaces for accountability and relationship-building. While the findings are exploratory and context-specific, they suggest that sustainable trust requires consistent police engagement in community life, youth-inclusive programs, and culturally responsive practices. Policy recommendations include institutionalizing youth-police councils at the barangay level, creating youth-accessible reporting mechanisms for misconduct, and supporting SK-led initiatives through local government and law enforcement partnerships.